Seroprevalence of ovine brucellosis in Bangladesh (Asian Journal of Medical and Biological Research, 2016)
An investigation was carried out to study the seroprevalence and risk factors for Brucella seropositivity in sheep in Bangladesh. For this, highly sheep populated ten different districts including all seven divisions of Bangladesh were selected where sheep of Panchagarh (151), Naogaon (101), Tangail (83), Noakhali (56), Sunamganj (52), Patuakhali (119) and Dhaka (75) were tested but sheep of Chapai Nawabganj, Khulna, Noakhali and Feni has under tested for Brucellosis. In the present study, seroprevalence of ovine brucellosis was tested by Rose Bengal Plate Test (RBPT), Serum Agglutination Test (SAT) and Enzyme-Linked Immunosorbent Assay (ELISA). About 5% sheep might have got Brucella infection. The highest Brucella antibody was observed in sheep of Tangail district (8.4%) followed by the sheep of Savar (8.0%), where as sheep of Subarna Char and Kala Para were free from Brucella antibody. In relation to age and sex, adults (6.5%) were more positive than young (3.6%) and female (5.3%) were more susceptible than male (3.8%).Asian J. Med. Biol. Res. March 2016, 2(1): 13-18